KAJIAN NILAI MANFAAT LANGSUNG EKOSISTEM MANGROVE DI KAMPUNG TANJUNG BATU KECAMATAN PULAU DERAWAN KABUPATEN BERAU - Sudesi; Erwiantono; Qoriah Saleha (Jurnal Pembangunan Perikanan dan Agribisnis, 2018)
The Mangrove ecosystem in Tanjung Batu village subdistric of Derawan Island had the natural resources potency that must be managed to gain ecology and economy benefits for the society. The purpose of research was 1) to identify the mangrove utilization by the society in Tanjung Batu village, 2) to analyze mangrove ecosystem economic value based on its use value and 3) to know society perception to mangrove ecosystem utilization pattern. The research was conducted from December 2017 to June 2018. The number of respondents was 65 persons that selected purposively, consisted of 35 fishermen and 30 community members. The use value of ecosystem mangrove was analyzed by consumer surplus and productivity methods, while the community perception analyzed descriptively. The result of study showed that the value of direct utilization of the mangrove ecosystem as a producer of fish and crab resources was Rp. 8.470.764.106/year.